Systematic review of the genera Rhabdostyla Kent 1880 and Orborhabdostyla Foissner et al. 2010 (Ciliophora, Peritrichia, Epistylididae) - Souza, Pedro Mendes De; Rossi, Mariana Fonseca; Dias, Roberto Júnio Pedroso (Zootaxa, 2024)
The genus Rhabdostyla is one of the oldest of the family Epistylididae, it was described over 120 years ago and has more than 40 species considered valid. This group went through several systematic changes throughout its existence and due to the lack of taxonomic information, said to be essential, for most species that compose it, some of these changes are still questioned. In order to better understand and validate the species and relationships identified for this genus, the present work makes a brief review for the genus Rhabdostyla and its related genera, Opisthostyla and Orborhabdostyla. A 18S-rDNA phylogenetic analysis was also performed to understand the relationship between these groups. As a result of this review, 45 diagnoses were compiled and reorganized for the current model, accompanied by new graphical representations for the species considered valid for the genus Rhabdostyla and its associates. The major changes that the genus underwent, such as synonymy and separation to a new genus, were discussed in light of new phylogenetic information, but despite this, other information is still needed for a better validation of these changes.